Electromagnetic Field and Total Loss Analysis of Transformers by Finite Element Method - Teke, Ibrahim Halil; ÖZÜPAK, Yıldırım; MAMİŞ, Mehmet Salih (International Journal of Engineering and Computer Science, 2019)
In the design of transformers, determining the optimum values ​​of the design parameters, the system in which the transformer will be used and the electrical power to be transferred are important for the continuity and safety of the system. It is very important for transformer design to know the electromagnetic field distribution and losses by creating electrical model of transformers. In this study, the theoretical, experimental and numerical analysis of the transformer were carried out. With the ANSYS @ MAXWELL-3D, simulations were carried out to determine the electromagnetic fields generated in transformer cores and windings for the purpose of efficient and safe operation of transformers. The results obtained during the study were calculated in real time. With the ANSYS @ MAXWELL-3D package software, the magnetic field and magnetic flux distribution of the transformer, especially in the case of transient events, are investigated. In addition, the core and copper loss of the transformer were examined experimentally, theoretically and numerically and comparisons were made. In this paper, by taking into consideration the electromagnetic field model, the core and winding design of the transformer were made and the equivalent circuit parameters were determined. In this study, short circuit test and open circuit test of transformers were carried out and field analyzes of transformers were performed and cores and copper losses were calculated and compared. The effect of ferromagnetic properties on core losses was determined, problem areas were determined, and the effect of magnetic field density and flux intensity on losses were determined. These results proved the accuracy of the FEM method used.